Pathways to Allah: Female Conversion to Islam in Australia. Issue 4 (2nd October 2017) - King, Ebony
ABSTRACT: This study investigates the motivations for female conversion to Islam in Australia. To capture the diverse motivations and individual spiritual transitions of female converts, a descriptive phenomenological methodology was employed. Empirical data are based on two in-depth, semi-structured hour-long interviews with each of six female converts living in South East Queensland and northern New South Wales. Five key motivations and experiences were common to all participants during their pathways to conversion. All of the converts expressed a prior belief in God; were drawn to Islam after meeting Muslims; engaged in a process of individual interpretation, reasoning or investigation of Islam ( ijtihād ) to arrive at their own understanding of Islamic belief and practice; felt the values, principles and beliefs resonated with their own prior convictions; and experienced challenges that provided resistance to their desire to become a Muslim, mostly connected with family, friends, lifestyle and the public sphere of everyday social interaction. This is the first phenomenological study to investigate female conversion to Islam in Australia and provides unique insight and further depth of understanding regarding female conversion to Islam in the West as well as the dynamics of Islam in Australia.